The Influence Of Politics And Economics Of The Media In Shaping Television Content In Post-Authoritarian Indonesia - Morissan, Morissan (2019)
The downfall of the last authoritarian ruler in May 1998 marked the beginning of the transition to democracy in Indonesia. After being curbed and controlled by the government for decades, a question arises, who actually controls media content in the era of liberalization. This research investigates how political economic factors in postauthoritarian era affect television workers and the content they produce, and two key questions raised: (1) How do political economic factors influence television workers in shaping their content?; (2) What is the most influential factor that affect television workers in shaping their content? This study uses both qualitative and quantitative methods. Quantitative method used is the survey whereas the main qualitative method used is interview combined with observation and documents by taking the views from within the media for the sake of triangulation to assure the validity of research. This research reveals important findings as the following: (1) Owners control, directly or indirectly, television workers in shaping content. The indirect control was made through senior executives. Owners sometimes involved directly in shaping content, especially entertainment program; (2) Advertiser also played significant role. It is common for television stations to get advertisers to help producing content. Stations may design sponsorship programs and directly solicit advertisers to provide funding for the content to produce; (3) Audience influence on television content is best presented on the use of rating reports in developing content. Most advertisers and television broadcasters depend on this audience feedback.